Direct and simultaneous observation of ultrafast electron and hole dynamics in germanium - Michael Zürch (Nature Portfolio, 2017)
Understanding excited carrier dynamics in semiconductors is central to the continued development of optoelectronic devices. Using extreme ultraviolet transient absorption spectroscopy, Zürchet al. directly and simultaneously observe ultrafast electron and hole dynamics in germanium thin films.